What Is Our Understanding of the Influence of Gut Microbiota on the Pathophysiology of Parkinson’s Disease? - Hill, Amaryllis E.; Wade-Martins, Richard; Burnet, Philip W. J. (Frontiers in Neuroscience, 2021)
Microbiota have increasingly become implicated in predisposition to human diseases, including neurodegenerative disorders such as Parkinson’s disease (PD). Traditionally, a central nervous system (CNS)-centric approach to understanding PD has predominated; however, an association of the gut with PD has existed since Parkinson himself reported the disease. The gut-brain axis refers to the bidirectional communication between the gastrointestinal tract (GIT) and the brain. Gut microbiota dysbiosis, reported in PD patients, may extend this to a microbiota-gut-brain axis. To date, mainly the bacteriome has been investigated. The change in abundance of bacterial products which accompanies dysbiosis is hypothesised to influence PD pathophysiology via multiple mechanisms which broadly centre on inflammation, a cause of alpha-synuclein (a-syn) misfolding. Two main routes are hypothesised by which gut microbiota can influence PD pathophysiology, the neural and humoral routes. The neural route involves a-syn misfolding peripherally in the enteric nerves which can then be transported to the brain via the vagus nerve. The humoral route involves transportation of bacterial products and proinflammatory cytokines from the gut via the circulation which can cause central a-syn misfolding by inducing neuroinflammation. This article will assess whether the current literature supports gut bacteria influencing PD pathophysiology via both routes